ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENUNJANG KEEFEKTIFITASAN PROSES PRODUKSI MEUBELAIR PADA PERUSAHAAN UD. JAYA ABADI PUTRA KEDUNGPRING LAMONGAN - Sandi Julianto (LPPM UNISDA, 2021)
: This research to determine the policy of controlling raw material inventory in a company if it uses the Economic Order Quantity (EOQ) method with current company policy. The data used in the form of data about the main raw material needs and the costs incurred in ordering and storing during 2017-2019. Data collection techniques by examining company documents. The research method used is descriptive discussion that is to make a systematic picture using the object under study. The results of the analysis are known to control raw material inventory at UD. Jaya Abadi Putra Kedungpring Lamongan can be concluded as follows (1) The optimal number of raw material inventory purchases using the economic order quantity method in 2017 is 176.93 m3 with a purchase frequency of 16 times, in 2018 amounting to 170.58 m3 with purchase frequency 16 times, in 2019 is 165.72 m3 with a purchase frequency of 16 times. And the total cost of raw material inventory of the company in the calculation of economic order quantity in 2017 is Rp. 962,606.69 in 2018 amounting to Rp. 1,063,484.4, in 2019 amounting to Rp. 1,112,250,3. (2). Safety stock / Safety Stock according to the results of the calculation of economic order quantity in 2017 is 29 m3, in 2018 is 24.33 m3, in 2019 is 19.84. Reorder points according to the calculation of economic order quantity in 2017 amounted to 57.14 m3, in 2018 amounted to 52.23 m3, in 2019 amounted to 46.96 m3.